ESCOLANO BENITO, A. (2017). La escuela como cultura. Experiencia, memoria y arqueología. Campinas: Editora Alínea, 328 páginas, ISBN 978-85-7516-792-2. - Rosa Ana Alonso Ruiz (Universidad de La Rioja, 2018)
ESCOLANO BENITO, A. (2017). La escuela como cultura. Experiencia, memoria y arqueología. Campinas: Editora Alínea, 328 páginas, ISBN 978-85-7516-792-2.